Variability of harvest loss in relation to physiological characteristics of cotton - Kazama, Elizabeth Haruna [UNESP]; Silva, Rouverson Pereira da; Carneiro, Franciele Morlin; Teixeira, Daniel de Bortoli; Vale, Welington Gonzaga do; Pereira, Gener Tadeu (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
Pearson's correlation and spatial variability are tools that can be used to help one understand the process of losses in the mechanical harvesting of cotton. Therefore, the objective of this study was to model the spatial distribution and map the losses of mechanical cotton harvest using geostatistics and to correlate the losses with agronomic variables using Pearson's correlation. The experiment was conducted in Itiquira and Lucas do Rio Verde, Mato Grosso State, Brazil. At each sampling point, the evaluated variables were agronomic plant variables and cotton losses in the soil and the plant (divided into lower, medium and upper thirds) and the sum total of losses. The highest losses in cotton harvest occurred in the lower third and on the soil, both of which exhibit a spatial dependence model, according to geostatistics, demonstrating that they do not occur in a randomized process and are related to the specific plant. There was a relationship between the plant populations with losses in the cotton crop. The plant population can influence the spatial dependence of losses.
Keywords: Gossypium hirsutum; geostatistics; precision agriculture